Fluid dynamics transactions. symposium, Jablonna, September 1961 - Fiszdon, Wadysaw (Pergamon Press, 1964)
Fluid Dynamics Transactions, Volume 1 is a compilation of papers presented at the Fifth Symposium on Fluid Dynamics held in Poland from August 26 to September 2, 1961. The symposium provided a forum for discussing developments in fluid dynamics based on the following topics: mathematical methods, hypersonic flow, rarefied gas dynamics, and magnetohydrodynamics. This volume is comprised of 26 chapters and begins by presenting equations for gas dynamics and highlighting some of applications of the general results. The discussion then turns to Cauchy's problem for the compressible flow of the sim.